The denitrifying anaerobic methane oxidation process and microorganisms in the environments: A review - Wei, Hengchen; Wang, Mengxin; Ya, Miaolei; Xu, Chaobin (Frontiers in Marine Science, 2022)
Methane (CH4) is an important greenhouse gas with a global warming potential 28 – 34 times that of CO2 over the 100-year horizon. Denitrifying anaerobic methane oxidation (DAMO) is a recently discovered process that potentially represents an important CH4 sink globally. This process involves two possible pathways: the nitrite-dependent DAMO mediated by NC10 bacteria and the nitrate-dependent DAMO by ANME-2d archaea. Both are widely detected in freshwater and coastal habitats using molecular tools. However, the distributions of these two processes and the functional microorganisms and their interactions with other N cycling pathways are far from clear. In this review, we conducted a scientometric analysis on a co-citation network consisting of 835 references derived from 354 citing articles closely related to the distribution of DAMO in the environment. Through this analysis, we found that current studies focus more on freshwater systems than coastal systems, and ANME-2d archaea are generally under-studied compared to NC10 bacteria. The emerging research topics in this area include AMO processes coupled to alternative electron acceptors and their role as CH4 sinks. We further reviewed papers focusing on DAMO distribution in freshwater and coastal environments guided by the result of the scientometric analysis. Finally, we identified several areas that require further research and proposed future research including comparisons of DAMO with other N cycling pathways and environmental conditions in the context of the river-estuary-sea continuum.